Micellization, interaction and thermodynamic study of butylated hydroxyanisole (synthetic antioxidant) and sodium dodecyl sulfate in aqueous-ethanol solution at 25, 30 and 35 °C - Varun Bhardwaj; Poonam Sharma; M.S. Chauhan; S. Chauhan (Journal of Saudi Chemical Society, 2016)
Surfactants are found to enhance the diffusion significantly depending on hydrophobic/hydrophilic group lengths and the structure of the surfactant molecule. Aggregation properties of sodium dodecyl sulfate (SDS) in the presence of butylated hydroxyanisole (synthetic antioxidant), at a range of temperatures (25, 30 and 35 °C) have been measured by the conductometric study in aqueous-ethanolic composite solution. The experimental data of aqueous-ethanolic solutions as a function of SDS concentration ranging from 1 to 14 mM dm−3 show the presence of inflexion points indicating micellization and interaction mechanisms. Effect of temperature was also observed in increasing the CMC (Critical Micelle Concentration) in the narrow composition. From the CMC values as a function of temperature, various thermodynamic parameters have been evaluated viz: (a) the standard enthalpy change (ΔHm°), (b) standard entropy change (ΔSm°), and (c) standard Gibbs energy change (ΔGm°). The results showed that the presence of alcohol, as well as the composition of water + ethanol may have effect on thermodynamic parameters. The variation in these parameters with the concentration of surfactant or with the change in temperature suggests the manifestation of hydrophobic interactions in the studied system.